Population pharmacokinetic analysis of zastaprazan (JP‐1366), a novel potassium‐competitive acid blocker, in patients and healthy volunteers - Eunsol Yang; Inyoung Hwang; Sang Chun Ji; John Kim; SeungHwan Lee (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Zastaprazan (JP‐1366) is a novel potassium‐competitive acid blocker for the treatment of acid‐related disorders. We aimed to establish a population pharmacokinetic (PK) model of zastaprazan, thereby characterizing the PK of zastaprazan in patients with gastroesophageal reflux disease (GERD) as well as evaluating the impact of various covariates, including CYP2C19 phenotypes, on zastaprazan PK. This population PK analysis included zastaprazan plasma concentration–time data from 92 patients with erosive GERD and 68 healthy volunteers without any gastrointestinal disorders and was performed using nonlinear mixed‐effect modeling. Simulations were conducted to predict zastaprazan PK under various dosing regimens in patients with GERD. The plasma PK of zastaprazan was adequately described by a two‐compartment model with Erlang‐type absorption (six sequential compartments) and first‐order elimination. CYP2C19 phenotypes had no significant effect on zastaprazan PK. The disease status was identified as a significant covariate on apparent clearance of zastaprazan, showing lower values in patients with GERD compared to healthy volunteers. However, the model‐based simulation indicated that the impact of disease status on zastaprazan exposure was not clinically meaningful. Overall, the current population PK model successfully characterized the observed zastaprazan PK in both patients with GERD and healthy volunteers.